Brucella abortus S19 GFP-tagged vaccine allows the serological identification of vaccinated cattle. - Carlos Chacón-Díaz (Public Library of Science (PLoS), 2021)
Bovine brucellosis induces abortion in cows, produces important economic losses, and causes a widely distributed zoonosis. Its eradication was achieved in several countries after sustained vaccination with the live attenuated Brucella abortus S19 vaccine, in combination with the slaughtering of serologically positive animals. S19 induces antibodies against the smooth lipopolysaccharide (S-LPS), making difficult the differentiation of infected from vaccinated bovines. We developed an S19 strain constitutively expressing the green fluorescent protein (S19-GFP) coded in chromosome II. The S19-GFP displays similar biological characteristics and immunogenic and protective efficacies in mice to the parental S19 strain. S19-GFP can be distinguished from S19 and B. abortus field strains by fluorescence and multiplex PCR. Twenty-five heifers were vaccinated withS19-GFP (5×109 CFU) by the subcutaneous or conjunctival routes and some boosted with GFP seven weeks thereafter. Immunized animals were followed up for over three years and tested for anti-S-LPS antibodies by both the Rose Bengal test and a competitive ELISA. Anti-GFP antibodies were detected by an indirect ELISA and Western blotting. In most cases, anti-S-LPS antibodies preceded for several weeks those against GFP. The anti-GFP antibody response was higher in the GFP boosted than in the non-boosted animals. In all cases, the anti-GFP antibodies persisted longer, or at least as long, as those against S-LPS. The drawbacks and potential advantages of using the S19-GFP vaccine for identifying vaccinated animals in infected environments are discussed.